Predictors of rapidly progressive interstitial lung disease and mortality in patients with autoantibodies against melanoma differentiation-associated protein 5 dermatomyositis. (14th February 2022) - So, Jacqueline; So, Ho; Wong, Victor Tak-Lung; Ho, Roy; Wu, Tsz Yuen; Wong, Priscilla Ching-Han; Tam, Lydia Ho-Pui; Ho, Chi; Lam, Tommy Tsz-On; Chung, Yuen Kwan; Li, Wai Ling; To, Chi Hung; et al.
Abstract: Objective: Anti-melanoma differentiation-associated protein 5 (MDA5)-positive DM is associated with rapidly progressive interstitial lung disease (RP-ILD) and high mortality. This multicentre retrospective study aimed to identify predictors of mortality and RP-ILD. Methods: Anti-MDA5-positive DM patients were identified from the Hong Kong Myositis Registry and the Clinical Data Analysis and Reporting System. Clinical characteristics were reviewed. Risk factors for mortality and RP-ILD were identified. Results: Among the 116 recruited patients, 100 (86.2%) had ILD, 47 (40.5%) had RP-ILD and 44 (37.9%) patients died. Cox regression analysis revealed RP-ILD [hazard ratio (HR) 9.735 (95% CI 3.905, 24.272)], age >52 years [HR 4.750 (95% CI 1.692, 13.333)], ferritin level >2800 pmol/l [HR 3.042 (95% CI 1.323, 6.997)] and lactate dehydrogenase (LDH) >400 IU/l [HR 2.290 (95% CI 1.009, 5.198)] were independent predictors of mortality. With regard to RP-ILD, analyses showed that potential predictors at baseline included age >50 years [HR 2.640 (95% CI 1.277, 5.455)], LDH >300 IU/l [HR 3.189 (95% CI 1.469, 6.918)], fever [HR 1.903 (95% CI 0.956, 3.790)] and neutrophil:lymphocyte ratio >7.0 [HR 1.967 (95% CI 0.942, 4.107)]. We proposed a prediction model based on fever, LDH, age and white cell count (FLAW) to stratify the risk of development of RP-ILD. The probability of RP-ILD in a patient with a score of 4 was 100%. A small internal validation cohort showed the odds of RP-ILD with FLAW scores of 0, 1, 2 and 3 were 0%, 0%, 42.9% and 75%, respectively. Conclusions: Anti-MDA5-associated RP-ILD is significantly associated with poor survival rates. The FLAW model maybe useful to predict the development of RP-ILD.